Analysis of the Sustainability Quality of Construction Industry Companies on the Quality of Disclosure of Sustainability Performance - Saputra, Handayani Jaka; Asyari, M.Ircham (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This study aims to analyze the sustainability quality of companies in the Construction Industry sector on the quality of disclosure of sustainability performance. The sample taken is 98 observations from all construction companies listed on the Indonesia Stock Exchange (IDX) that disclose sustainability reports or CSR. The quality of sustainability performance disclosures is assessed with the GRI Standard guidelines. This manual is the latest version issued by the Global Reporting Initiative (GRI), which can be implemented starting in 2021. The results showed that the economic, environmental, and social aspects did not have a significant influence on the company's profitability. The practical implication of this research is the urgency for the government not only to require sustainability reporting, but also to create a specific framework or indicator regarding sustainability in Indonesia. The implementation of sustainability finance will be more optimal if it is accompanied by disclosure guidelines that are in accordance with the business climate in Indonesia.